AWS technical essentials. - Wilkins, Mark R. (O'Reilly Media, Inc., 2019)
The cloud paradigm and cloud services providers are rapidly changing the way businesses and organizations of all types approach how they structure their IT environments. Amazon Web Services (AWS) has been a pioneer and dominant player in this realm since its inception, and it continues to be among the driving forces that are shaping the cloud today. If your organization is planning on or in the process of moving to the AWS cloud, you're going to want to be up to speed with the vast array of services that are available to you and how you can use them to best suit your particular needs. In this video course, designed for system administrators and developers as well as high-level managers, project managers, or anyone involved in cloud architecture, you will learn about the AWS concepts of cloud computing, namely Infrastructure as a Service (IaaS) and Platform as a Service (PaaS), forming a strong technical baseline. From there, you'll examine in detail how to work with AWS cloud services and become conversant with the various concepts that underpin the AWS framework. Students will learn the technical essentials of working in the AWS cloud; specifically, details on compute, storage, networking, and managed services offered by AWS. When you've completed this video course, you will know how these components all fit together. At the end of this course, you will fully understand Amazon cloud essentials and the key components, including compute, networking, storage, and management services. You will be capable of beginning to work with Amazon cloud services using the management console as well as understand AWS technology terms, networking concepts, scaling concepts, and have a strong grasp of cloud computing and what cloud computing is all about. By the end of this class you will be able to speak in proper "cloud speak" and, more important, understand the terminology. What you'll learn--and how you can apply it The core concepts underpinning the AWS cloud architecture Understand the functioning of the IaaS and PaaS models Specifics on compute, storage, networking, and managed services in AWS The essential technical facets of the AWS cloud environment This video course is for you because... You're a system administrator whose company is migrating to AWS in the near future You're a cloud architect responsible for designing AWS infrastructure You're an IT professional who needs to develop AWS technical knowledge and skills You're a developer who will be creating applications in the AWS cloud and need to learn about AWS IaaS and PaaS Prerequisites: You should have a technical background in networking, system administration, and working with virtualized resources You should have a strong interest in cloud technology You should have a solid understanding of computing Materials or downloads needed in advance: Readings (PDFs): AWS Compute Services AWS Global Services AWS Storage Services AWS Managed Services Introduction to automation at AWS Case study (a case study will be available before class along with the questions that will be asked during class) Videos: five-minute videos on AWS cloud services will be posted online in Safari Learning Availability Zones Choosing a Region Create a Custom VPC Public and Private Subnets Route Tables Creating Security Groups Adding an Internet Gateway Creating a custom AMI Creating Instances Creating launch templates Deploying EC2 Auto Recovery Understanding ELB Features EC2 Auto Scaling Creating EBS volumes Creating snapshots Creating S3 buckets Creating a lifecycle policy Creating IAM users and groups CloudWatch in operation Exploring CloudTrail events Creating EC 2 instances with Cloud Formation Deploying Elastic Beanstalk S3 buckets and alerts using Lambda Trusted Advisor Further resources: AWS Core Concepts AWS Managed Services AWS Core Design Services.